Pengaruh Pelayanan Pengurusan Dokumen Kapal terhadap Tingkat Kepuasan Pelanggan di PT Pertamina Port and Logistics Cabang Makassar - Jovanka Thiara Putri P; Faisal Saransi; Asnur Asnur (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Ship document processing services are an important factor in supporting smooth ship operations and influencing customer satisfaction. This study aims to analyze the quality of ship document processing services based on SERVQUAL dimensions and to determine their effect on customer satisfaction at PT Pertamina Port and Logistics Makassar Branch. This study used a quantitative method with an associative approach. The sample consisted of 47 respondents selected using total sampling technique. Data were collected through observation, questionnaires, and documentation, then analyzed using validity test, reliability test, descriptive statistics, simple linear regression, t-test, and coefficient of determination. The results showed that the quality of service was in the sufficient category with an average score of 40.79, while customer satisfaction was in the high category with an average score of 8.234. Ship document processing services had a positive and significant effect on customer satisfaction with a significance value of 0.000 < 0.05 and a contribution of 27.1%.